Wave-wise comparison of COVID 19 based on SARS-CoV-2 Variants of Concern (VOCs) in Bangladesh, India, Sri Lanka, Pakistan, Nepal and the probable reasons behind the less devastating effects of Delta variant in Bangladesh: a review - Hasan, Mahfuzul; Gupta, Somnath (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.